Proton Transfer Study of Low-Lying States of ¹³⁶La - Khan, Hasan Arif (My University, 1977)
The techniques of charged particle spectroscopy were utilized in studying the low-lying states of ¹³⁶La. Two proton transfer reactions were carried out on isotopically enriched targets of ¹³⁵Ba. Sixty-four energy levels of ¹³⁶La were observed up to an excitation of 1.8 MeV from ¹³⁵Ba(³He,d)¹³⁶La and ¹³⁵Ba(α,t)¹³⁶La reactions. Two methods were used to determine the ℓ-values for some of the states whose cross-sections could easily be obtained. One of the methods was to utilize the ratio of (³He,d) and (α,t) cross-section as an indicator of ℓ-values. The ℓ-values were also obtained from the angular distribution of the cross-sections of some of the multiplets.
The fore hand knowledge of the spin of the ground state made it possible to immediately assign spins to the first two excited states. Spins have also been assigned tentatively to a few other states using the 2J+1 rule.
In the process of this work, the relative Q-values for the ¹³⁴Ba(α,t)¹³⁵La, ¹³⁵Ba(α,t)¹³⁶La and ¹³⁶Ba(α,t)¹³⁷La reactions were also measured. The results show that the presently accepted proton separation energies for these lanthanum isotopes are considerably in error.
Keywords: Physics; Physics